Implementación de un sistema de video vigilancia mediante cámaras IP inalámbrico con dispositivos móviles para brindar seguridad a la asociación de comerciantes Cotopaxi sección la bahía del Cantón La Maná - Añarumba Coro, Luis Neptalí (2017)
The continuous process of technology in terms of security and surveillance systems has led to the great majority of households, businesses and institutions have the need to have equipment that facilitates the safeguarding of their establishments. The high levels of security problems in a particular place, today, have become unsustainable. That is why video surveillance is among the technologies most used by institutions, whether private or public, for the protection of both its facilities and its staff. In addition to helping to detect threats, cameras are installed in strategic areas so that aggression, theft and vandalism can be avoided. This research aims to implement a system of video surveillance through IP cameras with mobile devices, to provide security to the Cotopaxi Merchants Association, section of the Bay of the town "La Maná". For the development of the same it was used the exploratory research because it contributed to the familiarization with the problem, and the possible solution to pose immediately for the implementation of the system. In addition, experimental research, which facilitated the use of the principles found in the scientific method for the design of a machine, which will be developed in a rigorous and stealthily structured for the success of the experimentation. A survey was also conducted, where the majority of the respondents answered affirmatively. From the above, it is necessary to carry out a video surveillance system. In the implementation of the project the installation and configuration of the cameras and mobile devices was carried out, the same one that is visualizing the environment of the association, the router instead distributes the IP addresses for the exchange of information through the internet. The camera is the device that captures all the information, which can later be visualized. The mobile device allows access to be able to visualize from any place, where internet connection is available, within the association sector, if applicable, to have evidence of the damage or subtraction of the institutional material assets, and thus allow for the constancy of the event. Finally, this executed project contributes to the improvement of the security of the association and with technology that today are the most required.